Kontribusi Bakat Mekanik dan Motivasi Intrinsik terhadap Capaian Belajar Siswa di Era Revolusi Industri 5.0 - Supono Supono; Matrubi Matrubi; Muchlas Abror (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The Industrial Revolution 5.0 era requires Vocational High School (SMK) graduates to have competencies that are in line with the needs of the industry. However, there are still many students who struggle to achieve optimal learning outcomes. This study aims to analyze the contribution of mechanical talent and intrinsic motivation to student learning outcomes in the Motorcycle Engineering and Business Study Program, SMK Negeri 1 Kaligondang. A descriptive quantitative research method was used, with data analysis carried out using SPSS. The respondents consisted of 30 students, with instruments including questionnaires to measure mechanical aptitude and intrinsic motivation, as well as academic tests (pre-test and post-test) to assess learning outcomes. The findings revealed that mechanical talent contributed 4.7%, while intrinsic motivation contributed 4.51% to student learning outcomes. After an instructional intervention that focused on strengthening mechanical talent and intrinsic motivation, the number of students who failed to meet the minimum competency criteria (KKM) decreased from 16 to 4, with an increase in average scores from 65 to 85.74. These results confirm that improving cognitive and affective factors can significantly improve students' understanding of automotive engineering. Therefore, optimized learning strategies are essential for developing students' mechanical talents and intrinsic motivation, ensuring that vocational graduates are better prepared to face the challenges of the workforce.